Systemic inequities, dignity, and trust in the context of HIV care: a qualitative analysis - Amanda L. Sanchez; Chynna Mills; DeAuj’Zhane Coley; Katelin Hoskins; Florence Momplaisir; Robert Gross; Kathleen A. Brady; Rinad S. Beidas (International Journal for Equity in Health)
Abstract Adherence and retention in care are key targets to achieve favorable health outcomes for people with HIV. Challenges with adherence and retention are pronounced for marginalized communities facing intersectional structural oppression. Community health worker delivery of Managed Problem Solving (MAPS+), an evidence-based behavioral intervention, has the potential to improve adherence and retention, yet understanding structural inequities affecting people with HIV is necessary to increase the likelihood of equitable implementation. The current study explores systemic inequities influencing HIV care adherence and retention, and approaches to address these challenges. We conducted semi-structured interviews with 13 clinics and 4 constituent groups: prescribing clinicians, non-prescribing clinical team members (e.g., medical case managers), clinic administrators, and policymakers. Through reflexive thematic analysis within a constructionist paradigm, we identified two key themes. The first elucidated experiences of systemic inequities such as access to resources, healthcare system navigation difficulties, power differentials, medical mistrust, intersectional stigma and potential patient burden associated with MAPS+. The second theme highlighted the ways in which staff and clinicians shoulder the burden of addressing inequities by approaching people with HIV with dignity and developing trusting relationships and how MAPS + can bolster this approach by partnering with and centering patient needs. While these individual and organizational efforts are valuable, ending the HIV epidemic requires structural changes to address systemic inequities directly. This research underscores the complex interplay between structural oppression and HIV care, calling for comprehensive approaches to achieve health equity.